MOLECULAR DETECTION OF ASTROVIRUS USING REVERSE TRANSCRIPTASE QUANTITATIVE POLYMERASE CHAIN REACTION TECHNIQUE - & et al., Fadhil (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to highlight the importance of the melt curve-quantitative reverse transcriptase PCR (RT-qPCR) analysis in the detection of astrovirus (AstV) from both negative and positive rotavirus and enterovirus (EVs) samples, and the effectiveness of the AstV infection on the vaccine immunogenicity in the vaccinated infected children. By RT-qPCR based Sybre green associated- melting curve assay, stool samples of 49 enterovirus suspected patients and of 39 rotavirus suspected patients were tested for AstV. Results of EVs group showed a 29 (59.2%) positive AstV contributed to 26 (89.5%) co-infection with Evs and 3 (10.3%) as a single infection in negative samples for Evs. Furthermore, AstV co-infection percentage is higher than the single infection. Moreover, the percentage of the Astrovirus among the vaccinated AFP-suspected cases was 53%, while the percentage of these viruses among the unvaccinated was 100%. Thus, MamAstrovirus- 1 MK948878 is the first local isolate recorded in the Genbank. In conclusion, the RT-qPCR based on SYBR Green showed the rapid and efficient detection of AstV with few copies number. This allow to be used for the diagnosis of AstV along with other gastroenteritis viruses in a multiplex assay to reduce processing time.